PESANTREN POLICY MANAGEMENT IN STUDENT EMPOWERMENT FUNCTIONS - Silvia Fitri; Neng Lilis; Lutfiani Azhar; Zulfa Nafisa; Dita Fitria (MANAGERE : Indonesian Journal of Educational Management, 2021)
The study will discuss boarding policies for implementing its function as an empowering institution. The research was intended to find out how pestuous boarding policies are particularly interesting and to see how high the policy is. The research method used is the library research method that is a data gathering technique by conducting the study of books, literature, notes, and various reports relating to boarding policies in apostate encouraged function. The next discussion is to analyze the policy's no. 18 year 2019 law on boarding schools, particularly the chapter chapter on empowerment functions with swot analysis techniques that will examine the strengths, weaknesses, opportunities, and threats of the policy. The policy on government support listed in act number 18 in 2019 of boarding schools chapter 46 has the strengths and weaknesses of each in the application of the santri empowerment function.